Safety pharmacology of acute MDMA administration in healthy subjects - Vizeli, Patrick; Liechti, Matthias E (Journal of psychopharmacology (Oxford), 2017)
3,4-Methylenedioxymethamphetamine (MDMA; ecstasy) is being investigated in MDMA-assisted psychotherapy. The present study characterized the safety pharmacology of single-dose administrations of MDMA (75 or 125 mg) using data from nine double-blind, placebo-controlled, crossover studies performed in the same laboratory in a total of 166 healthy subjects. The duration of the subjective effects was 4.2 ± 1.3 h (range: 1.4-8.2 h). The 125 mg dose of MDMA produced greater 'good drug effect' ratings than 75 mg. MDMA produced moderate and transient 'bad drug effect' ratings, which were greater in women than in men. MDMA increased systolic blood pressure to >160 mmHg, heart rate >100 beats/min, and body temperature >38°C in 33%, 29% and 19% of the subjects, respectively. These proportions of subjects with hypertension (>160 mmHg), tachycardia, and body temperature >38°C were all significantly greater after 125 mg MDMA compared with the 75 mg dose. Acute and subacute adverse effects of MDMA as assessed by the List of Complaints were dose-dependent and more frequent in females. MDMA did not affect liver or kidney function at EOS 29 ± 22 days after use. No serious adverse events occurred. In conclusion, MDMA produced predominantly acute positive subjective drug effects. Bad subjective drug effects and other adverse effects were significantly more common in women. MDMA administration was overall safe in physically and psychiatrically healthy subjects and in a medical setting. However, the risks of MDMA are likely higher in patients with cardiovascular disease and remain to be investigated in patients with psychiatric disorders.